Using phenotypic correlations in the breeding evaluation of Hungarian Sport Horse mares - Posta, János; komlósi, István (Acta Agraria Debreceniensis, 2006)
The aim of this paper is to analyse phenotypic relationships between self performance test (SPT) parameters of Hungarian Sport Horse mares. Establishing these relationships may contribute to develop a breeding value estimation model. Data were given by the Association of Hungarian Sport Horse Breeders. The analysis is based on the SPT results of 3 and 4 year old mares from 1993 to 2004. Our aim is to determine practically explainable correlations among conformational traits (type, head, neck, saddle region, frame, forelegs, hind legs, regularity of movement, impulsion and elasticity of movement, overall impression); free jumping performance (jumping style, jumping ability, observation during training) and movement analysis traits (walk, trot, canter, overall impression, test rider’s score). A further aim is to determine correlations between free jumping performance and movement analysis traits.